Distributed output tracking control of nonlinear multi-agent systems with unknown time-varying powers. Issue 11 (2nd November 2022) - Li, Huijuan; Li, Wuquan; Gu, Jianzhong
Abstract : In this paper, we investigate the distributed output tracking problem for high-order nonlinear multi-agent systems (MASs) with unknown time-varying powers. For one leader case, by using the algebra graph theory and adding a power integrator, the distributed tracking control law is successfully designed to achieve that the tracking errors can be adjusted to be arbitrarily small, while ensuring that all the signals of the closed-loop system are bounded. Then we extend this result to the case of multiple leaders and solve the containment tracking problem, the designed distributed nonlinear controller can guarantee that the followers' outputs of the systems eventually converge to a limit point in the convex hull spanned by the leaders' outputs. Finally, two simulation examples are used to illustrate the effectiveness of the designed schemes.